The Relationship between Uric Acid Concentration and Some of Plasma Lipids in Patients with C. V. Disease in General Hospital of Al-Nasseriya - A. Al-Hussein Hassan, Hiba (Iraqi Journal of Pharmaceutical Sciences, 2017)
Cardiovascular disorders are refer to the class of diseases that involve the heart or blood vessels (arteries and veins). While the term technically refers to any disease that affects the cardiovascular system. Cholesterol is classified as a sterol (a contraction of steroid and alcohol).Although cholesterol is essential for life; high levels in circulation are associated with atherosclerosis. Triglyceride (more properly known as triacylglycerol , TAG or triacylglyceride) is a glyceride in which the glycerol is esterified with three fatty acids. It is the main constituent of vegetable oil and animal fats.High-density lipoproteins (HDL) is one of the 5 major groups of lipoproteins (chylomicrons, VLDL, IDL, LDL, HDL) which enable lipids like cholesterol and triglycerides to be transported in the blood stream. In healthy individuals, about thirty percent of blood cholesterol is carried by HDL. Uric acid (or urate) is non-protein nitrogen compound with the formula C5H4N4O3. This study aimed to determine the relation between uric acid, cholesterol, triglyceride and HDL-cholesterol concentration in cardiovascular disorders patients. Serum sample were collected from 84 cardiovascular disorders patients attended to the general hospital of Alnasseriya. All samples were analyzed for uric acid , cholesterol, triglyceride and HDL-cholesterol concentration by enzymatic-colorimetric method kits. The data showed a highly significant increased in the serum concentration of uric acid , cholesterol and triglyceride in cardiovascular disorders patients compared with healthy control (P<0.01) .In addition , there was no significant increased in the serum concentration of HDL-cholesterol in cardiovascular disorders patients compared with healthy control (P>0.05) .The data of this study strengthen the possibility that high concentration of uric acid may act as a risk factor in cardiovascular disease. Key words: high density lipoprotein (HDL-cholesterol),very low density lipoprotein(VLDL), low density lipoprotein(LDL),intermittent lipoprotein(IDL), hyperuricemia.